IMPROVING THE STUDENTS’ SPEAKING ABILITY USING ROLEPLAY AT 11th GRADE OF SMAN 12 MUARA BUNGO - Rozanita Harahap (Journal Of Language Education and Development (JLed), 2021)
This Classroom Action Research (CAR) was conducted to improve the students’ speaking ability using the roleplay. It was conducted at SMA N 12 Muara Bungo which involved the 11th grade students as the objects. The reseach found that using role play technique in teaching speaking was success to improve the students’ speaking skill. The criterion of action success is 75% of students could achieve the target score of the minimal mastery level criteria or KKM of English lesson was 76 (seventy six). At the beginning, there were 10 students or 35,71% of students in the class who achieved the standard criterion or KKM in pretest. And then, It was increased in the first cycle, there were 16 or 57,14% of students who achieved the standard criterion or KKM. In cycle 2, there were 24 or 85,71% students in the class who achieved the standard score (KKM). Not only that, based on the observation result showed that the students were braver and more confident in speaking, it is proved that the response of the students toward their interest in learning speaking using role play technique were 75.00% and 80.00% that means it falls into the good and very good category.